Quasi-cyclic fracture studies on stainless steel welded straight pipes with circumferential through-wall crack in the weld. (January 2017) - Vishnuvardhan, S.; Gandhi, P.; Raghava, G.; Pukazhendhi, D.M.; Saravanan, M.; Gupta, Suneel K.; Bhasin, Vivek; Vaze, K.K.
Abstract: Fracture studies were carried out on 170 mm OD welded straight pipes having circumferential through-wall crack in the weld under quasi-cyclic loading. The specimens were made of Type 304 LN stainless steel and welded using conventional Shielded Metal Arc (SMA) welding or Narrow Gap (NG) welding. The specimens were subjected to different amplitudes of load/displacement, which was decided based on the monotonic load carrying capacity of the specimens. It was found that the failure load reduces to 78.5% and 74.0% of the monotonic failure load for resisting 50 and 100 loading cycles, respectively in the case of NG welded pipes. The NG welded specimens showed more energy absorbing capability and crack growth resistance, when compared with SMA welded specimens. Crack growth was more stable in the case of specimens tested under displacement control; whereas the same was unstable in the case of load-controlled experiments and specimens failed by sudden collapse. Graphical abstract: Crack Growth during Quasi-cyclic Loading under Load Control. Highlights: Cyclic fracture behaviour of through-wall cracked welded straight pipes was studied. Cyclic failure load reduced to 78.5% of the monotonic failure load for resisting 50 loading cycles. NG welded specimens showed more energy absorbing capability and crack growth resistance. Crack growth under load-control was unstable and specimens failed by sudden collapse.